PMO-135 Zinc finger e-box binding homeobox 1 (ZEB1) induces epithelial to mesenchymal transition (EMT) and promotes tumour progression in hepatocellular carcinoma (HCC). (28th May 2012) - Sreekumar, R; Mirnezami, A; Wilson, H; Primrose, J; Thomas, G
Abstract : Introduction: HCC is the leading cause of cancer related mortality world wide. Emerging evidence suggests aberrant activation of an embryological trans-differentiation programme termed epithelial-mesenchymal transition (EMT) is critical in promoting metastasis in different carcinomas. We analysed the expression of ZEB1, a key transcription factor implicated in EMT, by immunohistochemistry (IHC) and western blotting in HCC. Additionally, we performed migration assays to analyse the consequences of ZEB1 expression in Huh7 and HepG2 cell lines. Methods: We performed western blotting for ZEB1, E-cadherin, vimentin and α-tubulin to identify the epithelial-mesenchymal status of eight primary HCC cell lines. IHC was undertaken on paraffin sections from 40 patients who underwent resections for primary HCC between May 1997 and November 2010 and scored by two independent pathologists. Clinicopathological data were collated retrospectively and patient survival calculated using the Kaplan–Meier method. We transfected ZEB1 into Huh7 and HepG2 cell lines by electroporation and assessed EMT related changes in cell motility using Boyden chambers (pore size: 8 μm) and serum as chemo-attractant. Results: Western blotting of proteins from eight HCC cell lines demonstrated reciprocal expression of ZEB1 and E-cadherin, suggesting EMT promotes a migratory phenotype in HCC. ZEB1 also significantly increased cell motility as a threefold increase in cell migration was observed after ZEB1 transfection into Huh7 cells (23±4 vs 79±5). ZEB1 positivity was detected in 11/40 specimens analysed by IHC. Statistical analysis highlighted ZEB1 as an independent prognostic marker favouring a significant reduction in cancer specific (41 vs 16 months, p Conclusion: Our results suggest that ZEB1 induced EMT promotes tumour progression and metastasis in HCC, and that over-expression of ZEB1 may represent an independent prognostic biomarker in patients with HCC. Competing interests: None declared.